SuperCooperators : the mathematics of evolution, altruism and human behaviour, (or, Why we need each other to succeed) /: the mathematics of evolution, altruism and human behaviour, (or, Why we need each other to succeed). (2011) - Nowak, M. A (Martin A.); Highfield, Roger
No abstract available